2015
DOI: 10.1504/ijfsnph.2015.070157
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxins in cassava (Manihot esculenta Crantz) and its products

Abstract: Contamination of foods with mycotoxins represents an important limit to the income of farmers and a major public health concern especially in tropical countries. Cassava represents an important part of the diet of many people in this part of the word and the most important smallholder crop in Africa. Fungal contamination of cassava products can occur at pre-harvest level or after, during processing, according to the conditions (moisture, temperature, competition with other microorganisms). Such fungal contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Recognition of the need to control aflatoxin contamination of food and feed grains has elicited various approaches from researchers to eliminate this toxin from maize and other susceptible crops. The approach to enhance host resistance through conventional means has gained renewed attention following the discovery of natural resistance to A. flavus infection and aflatoxin production in many crops like maize (Brown et al, 2001) cassava (Adjovi et al, 2015;Adjovi et al, i2014;Gnonlonfin et al, 2008) and cowpea (Houssou et al, 2009). In this last product, Houssou et al have proposed the presence of protein which confers this property to cowpea.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of the need to control aflatoxin contamination of food and feed grains has elicited various approaches from researchers to eliminate this toxin from maize and other susceptible crops. The approach to enhance host resistance through conventional means has gained renewed attention following the discovery of natural resistance to A. flavus infection and aflatoxin production in many crops like maize (Brown et al, 2001) cassava (Adjovi et al, 2015;Adjovi et al, i2014;Gnonlonfin et al, 2008) and cowpea (Houssou et al, 2009). In this last product, Houssou et al have proposed the presence of protein which confers this property to cowpea.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown the presence of aflatoxins in cassava products [5,23,24]. The study conducted by Jonathan et al [24] showed that major spoilage (biodeteriorating) fungi of Attiéké from Ejigbo, Iwo and Adjame in West Africa were mostly molds with Aspergillus niger and A. flavus having highest occurrence and Candida albicans and their percentage occurrence has direct effect on its food values.…”
Section: Resultsmentioning
confidence: 99%
“…The FAO estimates that 25% of the world food crops are contaminated by mycotoxin, of which the most notorious are the aflatoxins (AFTs) [4][5][6]. AFTs are metabolites produced primarily by the fungi Aspergillus flavus and Aspergillus parasiticus.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava is not generally associated with mould and aflatoxin contamination when fresh, due to the high moisture content and the presence of antiaflatoxin compounds [8]. Hence, it can be considered as a crop that is resistant to aflatoxin contamination during the preharvest period [9].…”
Section: Introductionmentioning
confidence: 99%
“…During fermentation Aspergillus spp. may produce aflatoxins under the right conditions of humidity, temperature, and pH [8,10]. A study by Gacheru et al found out that 87.5% of dried cassava in Nairobi, Kenya, had yeast and mould count bellow 3.0 Cfu g −1 , while in the coastal region, 60% of the samples had yeast and mould counts above the set limit [7].…”
Section: Introductionmentioning
confidence: 99%